Sex-specific associations between diet quality and mortality in adults with diabetes: findings from NHANES 2001-2018 - Youqi, Zhang; Meng, Yan; Liu, Ji; Jianjun, Wu; Fan, Yang (Frontiers in Nutrition, 2025)
ObjectiveTo investigate the impact of diet on cardiovascular (CV)/all-cause mortality among individuals with diabetes, and to explore whether this relationship changes by gender.MethodsWe collected data from the National Health and Nutrition Examination Survey (NHANES) database pertaining to 5,875 individuals with diabetes (3,068 males and 2,807 females) and used the Healthy Eating Index (HEI), the Alternative Healthy Eating Index (AHEI), and the alternative Mediterranean Diet (aMED) index to assess diet quality. Multivariate Cox models were used to determine the association between dietary quality scores and CV/all-cause mortality, stratified by genders. Dose–response relationships were assessed using the Restricted Cubic Spline (RCS). As a secondary objective, a further analysis was conducted on the connection between CV/all-cause mortality and different dietary components.ResultsDuring a median 9.25-year follow-up period, we observed 1,488 all-cause deaths, including 486 CV deaths. Sex-stratified analyses revealed that higher diet quality, as indicated by each standard deviation increase in the score, was significantly associated with a reduced risk of cardiovascular mortality in males (p < 0.05). No significant associations were observed in females (p > 0.05). Among the component scores of the aMED, legume intake was unfavorable for males with diabetes but was remarkably associated with lower CV/all-cause mortality in females.ConclusionIn the diabetic population, high dietary scores are significantly associated with lower CV/all-cause mortality in males but not in females.